TRADISI UANG ILANG SEBAGAI HUKUM ADAT DALAM PELAKSANAAN PERNIKAHAN DI NAGARI CAMPAGO SELATAN - Riyen Gusti Suparta (JURIS (Jurnal Ilmiah Syariah), 2018)
The Lost Money or Given Money” is called Uang Ilang in term of Minangkabau culture. It is a gift in the form of a sum of money by the bride and groom given to the prospective bridegroom. The payment of “the lost money” is done through intermediary the head of the tribe between the two sides of the family. This tradition of “the lost money” is a customary requirement that must be met by the family of the bride to the prospective groom. The amount of money may vary depending on the request of the head of the tribe or the male family to the prospective bride. There are two aspects that determine the amount of money payments first, the cultural aspects and socioeconomic status. The purpose of this study is to describe how the implementation of traditions of “the lost money” in South Campago District. This research used descriptive method with qualitative approach. Data collection by interview and supported by supporting books related to “the lost money”. The result of this research is known that marriage with “the lost money” tradition system is customary law that has been applied to South Campago District community. In the implementation by finding the source of “the lost money” by borrowing, participation from the head of the tribe, helps from the groom if the couple is dating and t”the lost money” be the responsibility of the parents. The high low payment of illicit money for now is also influenced by the social status of the prospective bridegroom but most of the people do traditions of “the lost money” more to the cultural aspect so the number of payers is only as a customary filler only.